2021
DOI: 10.1186/s40814-020-00754-3
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring in older people with diabetes receiving home care—a feasibility study

Abstract: Background Hypoglycemic incidents in older people can cause severe health problems, enhance general age-related disabilities, and cause frailty. Little is known about incidences of hypoglycemia in older home-dwelling people with diabetes. Thus, the aim of this study was to examine the feasibility of capturing hypoglycemia and issues associated with increased risk of hypoglycemia by use of continuous glucose monitoring (CGM) and standardized questionnaires among older home-dwelling individuals w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…On the other hand, a recent study showed that CGM data from 7 days compared with 14 days did not show significant differences in glucose management indicators [ 38 ]. The results from the published feasibility study [ 39 ] showed that a five-day period was sufficient to produce relevant data. Moreover, the five-day study period allowed for conducting the CGM measures primarily on weekdays.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent study showed that CGM data from 7 days compared with 14 days did not show significant differences in glucose management indicators [ 38 ]. The results from the published feasibility study [ 39 ] showed that a five-day period was sufficient to produce relevant data. Moreover, the five-day study period allowed for conducting the CGM measures primarily on weekdays.…”
Section: Discussionmentioning
confidence: 99%
“…Telehealth applications enable reduction of the information gap between medical experts and patients. Since it can be applied to diverse fields and specialties, its usefulness has been reported for both diagnosing and monitoring various medical conditions [5–12] . Telehealth is also widely used for monitoring various cardiac diseases [13–16] and, regarding patients with CIED, has been used for remote monitoring [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Since it can be applied to diverse fields and specialties, its usefulness has been reported for both Hwang and Kim Medicine (2022) 101:23 Medicine diagnosing and monitoring various medical conditions. [5][6][7][8][9][10][11][12] Telehealth is also widely used for monitoring various cardiac diseases [13][14][15][16] and, regarding patients with CIED, has been used for remote monitoring. [17] The extent of RM of CIEDs goes beyond monitoring the device parameters and providing information on patients' condition.…”
Section: Discussionmentioning
confidence: 99%